The microbiology of fermented shrimps (Nematopalaemon tenuipes) of Cagayan - Culasing, Carmencita Lorenzo
Shirmps of Cagayan locally known as aramang were utilized for this study, which was done in three Phases. Phase 1 dealt with the microbiology of aramang right after catching and prior to salting. Phase II dealt with the microbiology of bagoong aramang prepared according to the procedure of Nieto (1982) and Phase III was concerned with the determination of the effect of inoculating bacteria identified in Phase 2. The aramang stored for 7 hours after catching prior to salting was evaluated to be good. It had a pH of 7.8 a slight loss of both shrimp odor and shrimp flavor. Bagoong aramang which wa prepared according to Nieto, initially had 9 different kinds of colonies, 7 of which were bacteria and two which were molds. The seven bacteria isolated were Pseudomonas, Halobacteriom, Micrococcus (orange and yellow) Acromabacter, Halococcus and Pediococcus and the isolated 2 molds were Aspergillus and Pennicillium. The 9 different colonies isolated were only survivor of the original flora. However, during the fermentation process only three were observed to be present: Halococcus, Pediococcus and Acromobacter. Inoculating the newly prepared bagoong aramang with the isolated and identified bacteria in Phase 2 did not improve the quality of bagoong aramang. There was no effect on he pH, titrable acidity and on salt content. Relative to sensory characteristics, the inoculated samples did not show any improvement compared to the control.